Pemberdayaan Masyarakat Melalui Pengolahan Air Nira Aren Menjadi Minuman Kemasan yang Bernilai Ekonomis di Desa Gelangsar Kabupaten Lombok Barat - Juniawan, Alvin; Syuhriatin, Syuhriatin; Rosadi, Narita Amni (Jurnal Pengabdian UNDIKMA, 2025)
This Community Service aims to improve the knowledge and skills of the members of the "Batu Beleq" farmer group in processing Palm Water into Packaged Drinks with Economical Value. The method of implementing this service used training through the stages of survey, socialization, and practice. The participants of this service were the Palm Farmer group in Gelangsar Village, West Lombok Regency with a total of 30 participants, involving students of the Faculty of Science and Agriculture. The results of this service showed the increased knowledge and skills of participants in processing palm water using packaging tools and UV light sterilization without additional chemicals. In addition, participants had the ability to package palm water products that are durable and long lasting.